The Relationship Between Service Quality and Consumer Satisfaction Link: Does Perceived Value Have a Mediating Effect? : An Evidence from Mutual Fund Company in Jakarta - Hutagaol, Ronald Marthin; Basbeth, Firdaus (Directorate of Academic Research and Community Services, 2021)
Despite the growing number of millennials and fintech having been present for some years now in mutual funds in Jakarta, the market share of PT PAM Indonesia has not increased. The number of unhappy customers reflected by the number of inactive customers has been increased to 43% of its total customers. due to the disappointment with the company’s services. This study is investigating the influence of service quality on consumer satisfaction and consumer perceived value as a mediating variable in mutual funds in Jakarta. This study contributes to the customer's perceived value literature by providing evidence in the mutual fund industry. To gather the primary data, in this study using a quantitative approach by sending a questionnaire to 100 millennials customers. SPSS software was used to analyze the satisfaction level in different locations and demographic factors, whilst SmartPLS3 was used to analyze the relationship between variables and to test hypotheses. The result showed that consumer perceived value mediates the relationship between service quality on consumer satisfaction. The findings suggest to retrieve customer satisfaction, the company must improve its service quality to meet consumer perceived value especially for the millennials in the mutual fund industry.